Effects of chronic kidney disease on clinical outcomes in patients with peripheral artery disease undergoing endovascular treatment: Analysis from the K-VIS ELLA registry. (1st July 2018) - Kim, Hyung Oh; Kim, Jae-Min; Woo, Jong Shin; Choi, Donghoon; Ko, Young-Guk; Ahn, Chul-Min; Lee, Seung-Whan; Lee, Jae-Hwan; Choi, Seung-Hyuk; Yu, Cheol Woong; Min, Pil-Ki; Yoon, Chang-Hwan; et al.
Abstract: Objectives: Chronic kidney disease (CKD) is a risk factor for peripheral artery disease (PAD), but the impact of CKD in PAD patients who received endovascular treatment (EVT) is not well studied. Aim of this study is to clarify the impact of CKD in patients with PAD in real EVT era. Methods: Using the Korean Vascular Intervention Society (K-VIS) endovascular therapy in lower limb artery disease registry (ELLA) registry, we analyzed 3434 patients who underwent EVT. Baseline characteristics, in-hospital events, and overall- and major adverse limb events (MALE)-free survival were analyzed. Results: 2739 patients (3548 target limbs) were included. 272 patients featured CKD (9.9%). Limbs in CKD patients had higher Rutherford scores, higher prevalence of critical limb ischemia (CLI). There were no differences in technical success rates in non-CKD vs. CKD group comparison and non-severe CKD vs. severe CKD group comparison (p = 0.050, 0.581, respectively). In-hospital death (p < 0.001) and short-term unexpected amputation (p = 0.028) were more frequent in the CKD group. The short-term outcome differences between severe and non-severe CKD were insignificant. Kaplan–Meier curves favored overall and MALE-free survival in non-CKD patients compared with CKD patients, but there was no difference in overall- or MALE-free survival between non-severe CKD and severe CKD groups. Conclusion: PAD patients with CKD showed worse short-term mortality, short-term unexpected amputation outcome, and overall- and MALE-free survival than those without CKD in real EVT era. These findings might provide additive prognostic information for PAD patients with CKD who will be treated with EVT. Highlights: EVT has become one of the primary options in treating PAD these days. We analyzed recent multicenter retrospective data of EVT received PAD patients. Our population showed short-term adverse impact in patients with CKD. Our data also showed worse long-term event-free survival in patients with CKD. CKD may be considered as important prognostic factor in EVT procedure in EVT era.